Using artificial text to personalize e-learning - Segizbay, M. B.; Kozhamkulova, Zh. Zh.; Togzhanova, K. O. (Харківський національний автомобільно-дорожній універститет, 2024)
In the context of modern technological dominance at all levels of life, universal solutions are becoming insufficient. Consumers are demanding “personalization”, and companies are adapting to these requests to make their products and services more attractive to a specific audience. In education, this is manifested in the creation of a learning environment where students can manage their own learning. E-learning, based on information and communication technologies, has become popular in recent years. To achieve the best results in such learning, its personalization is necessary, which can be effectively achieved with the help of artificial intelligence technologies. The purpose of this paper is to study the possibilities of using artificial intelligence technologies for personalization of e-learning. The methods of comparative and system analysis, as well as a logical approach, were used. The article discusses key approaches to personalized learning and the features of personalization in the context of e-learning. An analysis of the possibilities of using artificial intelligence in this area was conducted, and conclusions were made that such technologies can simplify the process of personalized elearning without increasing the workload of teachers.
Keywords: educational process; personalization; e-learning; virtual educational environment; artificial intelligence; personalized educational technology systems; 004.032.3